Strategi Dalam Menciptakan Kesejahteraan Masyarakat Melalui Rekonstruksi APBN: Telaah kritis dari Kitab Al-Amwal - Syamsuri Syamsuri (ITB AAS INDONESIA Surakarta, 2021)
There are at least two approaches taken by the government to deal with the problem of poverty or create prosperity, namely through fiscal policy and monetary policy. In this article, the author will examine the fiscal policies that should be carried out by the government using the reallocation method of state revenue and expenditure funds or the so-called APBN. Several Muslim figures have studied the problem solving, such as, As-Syaibani and Umar bin Abdul Aziz. However, the author focuses on the contribution of Muslim scholar who was born from Byzantine descent in 154/1858, namely Abu Ubaid, his brilliant idea as outlined in the book Al-Amwal in order to create the mashlahat of society in a country. By using a qualitative method with the library research approach and assisted by the final character study approach, it can be concluded that some strategies according to Abu Ubaid are a solution in creating social welfare, namely Zakat, fa'I, khumus, kharja, and jizyah. As well as regarding the import and export of goods, Abu Ubaid uses a strategy of not having zero tariffs in international trade, excise on staples is cheaper, and there are certain limitations to be subject to excise. This means that when goods enter into a country, there is a cut or excise that enters zakat.